Analisis Efisiensi Sistem SCADA Dalam Monitoring Dan Data Logging Pada Plant Water for Injection (WFI) di Large Volume Parenteral (LVP) PT. Sanbe Farma - Najmurrokhman, Asep; Bunga Wahyudiani; Azmi Hafizat Muzada (Department of Electrical Engineering, UNJANI, 2025)
The Supervisory Control and Data Acquisition (SCADA) system is essential in pharmaceutical manufacturing, particularly for ensuring product quality and operational continuity in the Water for Injection (WFI) process at the Large Volume Parenteral (LVP) facility of PT Sanbe Farma. This study evaluates the efficiency and performance of SCADA in monitoring and logging WFI flow rate and conductivity. The assessment involves real-time data observation, historical trend analysis, efficiency measurement, and performance evaluation based on data availability, logging reliability, sampling frequency, event detection, and value consistency. Findings show that SCADA achieved 100% data availability for all monitored parameters, with a performance index consistently above 96%, indicating strong capability for real-time anomaly detection and uninterrupted data recording. Flow-rate monitoring efficiency reached 85% in May 2025 but declined to 70% in June 2025 due to process issues. In contrast, conductivity monitoring in both Cold and Hot loops remained highly efficient, exceeding 99%. Statistical results also revealed a 100% variability index and a high peak-to-average ratio, demonstrating the system’s accuracy in capturing dynamic fluctuations. Overall, the SCADA system in PT Sanbe Farma Unit 3 provides reliable monitoring performance and supports early disturbance detection, making it a strong basis for system maintenance and improvement.